Diagnosing to intervene: Diagnostic activities as pedagogical tools to reflect on the teaching of written production - Dodó , Walisson (Seven Editora, 2023)
The objective of this report is to present the results of a diagnostic activity of written production, having as textual genre selected the writing of the Enem. Methodologically, I made use of Action Research to carry out the activity (THIOLLENT, 2011). The analysis revealed that diagnostic activities, when well used, can be consolidated as an important pedagogical device capable of helping us reflect on the teaching and learning of written production in school.DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-089